Lithium supplementing material, positive electrode sheet including same, electrochemical device, and electronic device
Patent Information
- Application Number
- CN202511743380.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-11-25
AI Technical Summary
为此,本申请提出一种补锂材料及包括其的正极片、电化学装置和电子设备,旨在解决目前正极补锂材料存在的在高电压下运行或高温存储过程中可能导致的产气、胀气现象,进而导致电池性能恶化的问题
[0005]本申请旨在至少解决现有技术中存在的技术问题之一。为此,本申请提出一种补锂材料及包括其的正极片、电化学装置和电子设备,旨在解决目前正极补锂材料存在的在高电压下运行或高温存储过程中可能导致的产气、胀气现象,进而导致电池性能恶化的问题。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical energy storage technology, and in particular to a lithium replenishment material and a positive electrode, electrochemical device and electronic device including the same. Background Technology
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and lack of memory effect. However, during the first charge and discharge cycle, the electrolyte decomposes on the negative electrode surface, forming a solid electrolyte interphase (SEI) film. This permanently consumes some lithium ions from the positive electrode, resulting in a lower coulombic efficiency (ICE) during the first cycle, thus reducing the battery's capacity and energy density. Furthermore, during cyclic storage, the consumption of active lithium also leads to capacity decay, further reducing battery life.
[0003] In related technologies, with the increasing demand for high energy density and long cycle life of batteries, solutions for optimizing battery performance are constantly being explored. Among these, cathode lithium replenishment technology has become an important research direction. Cathode lithium replenishment technology refers to the timely injection of lithium ions into the battery during the cycling process of a lithium-ion battery to solve the problem of lithium ion consumption under long-term use or high voltage. Accordingly, adding cathode lithium replenishment materials to the battery cathode material can effectively provide lithium ions, compensate for lithium loss during the discharge process, thereby extending the battery's lifespan and improving energy density. Cathode lithium replenishment technology provides new opportunities for improving battery performance. However, in some demanding application scenarios, such as high-voltage lithium-ion battery applications, new challenges are posed to cathode lithium replenishment technology: In high-voltage lithium-ion batteries, common cathode materials such as lithium cobalt oxide and nickel cobalt manganese oxide are prone to gas expansion after using lithium replenishment materials under long-term high-voltage operation, leading to battery performance degradation; moreover, gas generation may also occur during high-temperature storage, which will also cause battery performance degradation.
[0004] Therefore, it is of great significance to solve the problem of gas generation and expansion that may occur during operation at high voltage or storage at high temperature in current cathode lithium replenishment materials, which leads to the deterioration of battery performance, and to provide a lithium replenishment material with strong stability, excellent performance in demanding application scenarios, and the ability to improve the cycle stability and high temperature performance of the cathode. Summary of the Invention
[0005] This application aims to address at least one of the technical problems existing in the prior art. To this end, this application proposes a lithium replenishment material and a positive electrode sheet, electrochemical device, and electronic device including the same, aiming to solve the problem that current positive electrode lithium replenishment materials may cause gas generation and expansion phenomena during high-voltage operation or high-temperature storage, which in turn lead to the deterioration of battery performance.
[0006] In a first aspect, this application provides a lithium replenishment material comprising a core, a first coating layer, and a second coating layer, wherein the first coating layer coats the surface of the core, and the second coating layer at least partially coats the surface of the first coating layer; the core comprises lithium silicon oxide; the material of the first coating layer comprises a carbon material; and the material of the second coating layer comprises lithium silicon metal oxide.
[0007] The lithium replenishment material according to the embodiments of this application has at least the following beneficial effects: This application proposes a lithium replenishment material comprising a composite structure formed by a core, a first coating layer, and a second coating layer. The core is made of a lithium, silicon, and oxygen-based compound, which can improve the cycle stability and high-temperature performance of the positive electrode. The first coating layer is a uniform coating formed of carbon material, which not only isolates external moisture and carbon dioxide but also improves electronic conductivity. The second coating layer is an incomplete coating formed of lithium silicon metal oxide, which is dotted and dispersed on the surface of the material, reducing residual alkali on the surface of the lithium replenishment material and providing a higher irreversible active lithium content. The lithium replenishment material with the above-mentioned composite structure not only provides lithium-ion supply during the delithiation process but also improves the electrochemical stability of the positive electrode active material (e.g., lithium cobalt oxide), helping to avoid unnecessary side reactions with the electrolyte. Simultaneously, this lithium replenishment material has a high specific capacity, effectively improving the energy density of lithium-ion batteries. Furthermore, the selection of carbon sources and different metals in this lithium replenishment material lowers the core decomposition potential, enabling the delithiation reaction to complete within the normal operating voltage range of lithium-ion batteries. Ultimately, by optimizing the design of the lithium replenishment material, this application significantly improves the overall performance of lithium-ion batteries, making them perform better in demanding applications. It not only exhibits good high-temperature storage and thermal performance but also maintains excellent high-temperature storage and high-temperature cycling performance at high voltages, demonstrating extremely broad application prospects in the field of rechargeable batteries.
[0008] In some implementations, the first coating layer completely covers the surface of the core.
[0009] In some implementations, the median particle size Dv of the kernel 50 The content of the first coating layer as a percentage of the mass fraction W1 of the lithium replenishment material, and the coating distribution density C of the second coating layer satisfy the following relationship: 3 ≤ C / Dv 50 ×W1≤9, where Dv50 The unit is μm, the unit of W1 is %, and the unit of C is %.
[0010] In some embodiments, the lithium replenishing material includes at least one of the following (a1) to (a9): (a1) The lithium silicon oxide includes Li x Si y O z Where 0 < x < 10, 0 < y ≤ 5, 0 < z ≤ 12, and x, y, and z are all integers; (a2) When (a1) is included, the lithium silicon oxide includes at least one of lithium monosilicate, lithium disilicate, lithium trisilicate, lithium tetrasilicate, and lithium pentasilicate; (a3) When (a2) is included, the lithium silicon oxide includes Li8SiO6, Li4SiO4, Li2SiO3, Li6Si2O7, Li2Si2O5, Li2Si3O7, Li4Si3O8, Li4Si4O4, and Li2Si5O. 11 At least one of them; (a4) The median particle size Dv of the kernel 50 The range is 0.1~3μm; (a5) The carbon material includes at least one of biocarbon, conductive carbon, graphene, and carbon nanotubes; (a6) The content of the first coating layer as a percentage of the mass fraction W1 of the lithium replenishment material is in the range of 0 < W1 ≤ 10%; (a7) The lithium silicon metal oxide includes Li2N d Si (2-d) O4, wherein 0 < d ≤ 0.5, and N is selected from at least one of Na, Mg, and Al; (a8) The content of the second coating layer as a percentage of the mass fraction W2 of the lithium supplementation material is in the range of 0 < W2 ≤ 2%; (a9) The coating distribution density C of the second coating layer is in the range of 20~70%.
[0011] A second aspect of this application provides a cathode material, comprising a cathode active material and the aforementioned lithium supplementation material; the cathode active material comprises lithium cobalt aluminum oxide.
[0012] In some embodiments, the positive electrode material includes at least one of (b1) to (b4): (b1) The lithium cobalt aluminum oxide includes LiCo (1-x-y) M x Al yO2, where 0 < x ≤ y ≤ 0.05, and M is selected from at least one of Mg, Ti, Zr, Co, Zr, Mn, Y, La, Sr, W, and Sc; (b2) In the cathode material, the content of aluminum element accounts for W of the mass fraction of the cathode material. A The range is 10,000 to 20,000 ppm; (b3) In the cathode material, the content of silicon element accounts for W of the mass fraction of the cathode material. B The range is 150~950ppm; (b4) In the cathode material, the content of aluminum element accounts for W of the mass fraction of the cathode material. A The content of silicon element as a percentage of the mass fraction of the cathode material, W B The ratio satisfies the following relationship: 16 ≤ W A / W B ≤66.6.
[0013] A third aspect of this application provides a positive electrode sheet, comprising a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, the positive active material layer comprising the aforementioned positive electrode material.
[0014] A fourth aspect of this application provides a battery cell, including a negative electrode and the aforementioned positive electrode.
[0015] A fifth aspect of this application provides an electrochemical device comprising the aforementioned battery cell.
[0016] A sixth aspect of this application provides an electronic device comprising the electrochemical device described above. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. The embodiments of this application may omit unnecessary detailed descriptions. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art. In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features. As used herein, the terms “approximately,” “generally,” “substantially,” and “about” are used to describe and indicate small variations. When used in conjunction with an event or situation, the terms may refer to examples in which the event or situation occurred precisely and examples in which the event or situation occurred very approximately. For example, when used in conjunction with numerical values, the terms may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. For example, if the difference between two values is less than or equal to ±10% of the average of the values (e.g., less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%), then the two values can be considered "substantially" the same. Additionally, quantities, ratios, and other numerical values are sometimes presented in range format in this document. It should be understood that such range format is for convenience and brevity and should be interpreted flexibly to include not only the numerical values explicitly specified as range limits, but also all individual numerical values or subranges covered within the range, as if each numerical value and subrange were explicitly specified. In the detailed description and claims, a list of items connected by the terms "one of," "among," "a kind of," or other similar terms may mean any of the listed items. For example, if items A and B are listed, then the phrase "one of A and B" means only A or only B. In another example, if items A, B, and C are listed, then the phrase "one of A, B, and C" means only A; only B; or only C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements. In the detailed description and claims, the list of items connected by the term "at least one of" can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. In the following description, all figures disclosed in this application are approximate values, regardless of whether the terms "about" or "approximately" are used in conjunction. They may vary by 1%, 2%, 5%, or sometimes 10% to 20%. Whenever a range of values with a lower limit (RL) and an upper limit (RU) is disclosed, any values falling within that range are specifically disclosed. Specifically, the following values within this range are specifically disclosed: R = RL + k * (RU - RL), where k is a variable with a 1% increment from 1% to 100%, i.e., k is 1%, 2%, 3%, 4%, 5%, ..., 50%, 51%, 52%, ..., 95%, 96%, 97%, 98%, 99%, or 100%. Furthermore, any range of values defined by the two R values as defined above are also specifically disclosed. Throughout this specification, references to "implementation," "partial implementation," "one implementation," "another implementation," "specific method," or "partial method" mean that at least one implementation or embodiment in this application includes the specific features, structures, materials, or characteristics described in that implementation or embodiment. In this application, numerical ranges are involved. Unless otherwise specified, the numerical ranges mentioned above are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form a range not explicitly stated. Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the invention, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the invention.
[0018] The term "polymer" refers to a polymeric compound prepared by polymerizing the same or different types of monomers. The general term "polymer" includes the terms "homopolymer," "copolymer," "trimer," and "interpolymer." The term "coating" refers to one or more layers applied to one or both sides of a porous substrate material. Functional coatings comprise a mixture of at least one organic binder and at least one inorganic filler. In addition to the organic binder and inorganic filler, the protective porous layer may also include one or more additives. Functional coatings can be single-layer, double-layer, or multi-layer structures. The term "binder" refers to a substance used to bond inorganic fillers to or to each other in a porous substrate material. Any organic binder that can bond inorganic fillers to or to each other in a porous substrate material may be used herein. Some non-limiting examples of organic binders include polyesters, polyamides, polyacrylic acid, polyethers, polyimides, polyolefins, rubbers, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, cellulose, cellulose derivatives, latexes, and combinations thereof.
[0019] The term "inorganic filler" refers to a non-conductive material. Some non-limiting examples of inorganic fillers include metal oxides, as well as non-oxide materials and non-metallic materials. Some non-limiting examples of metal oxides include alumina, zirconium oxide, barium titanate, lead zirconate titanate, ferrites, zinc oxide, and combinations thereof. Some non-limiting examples of non-oxide materials and non-metallic materials include silicon carbide, silicon nitride, aluminum nitride, boron nitride, titanium boride, molybdenum silicide, and combinations thereof. The term "water-soluble polymer" refers to a high molecular weight polymer that is soluble in water or uniformly dispersed in water. The term "oil-soluble polymer" refers to a high molecular weight polymer that is soluble in water or uniformly dispersed in an organic polar solvent, including but not limited to N-methylpyrrolidone (NMP) and dimethyl sulfoxide (DMSO).
[0020] Positive electrode active material: As used herein and in the claims, the term "positive electrode active material" (also known as cathode active material) is defined as a material that is electrochemically active in a positive electrode or cathode. Active material should be understood as a material capable of capturing and releasing Li and / or Na ions when subjected to voltage changes over a predetermined time period.
[0021] <Lithium Supplement Materials> In a first aspect, this application proposes a lithium replenishment material, which includes a core, a first coating layer, and a second coating layer. The first coating layer coats the surface of the core, and the second coating layer coats at least partially the surface of the first coating layer. The core includes lithium silicon oxide; the first coating layer includes a carbon material; and the second coating layer includes lithium silicon metal oxide.
[0022] The lithium replenishment material according to the embodiments of this application has at least the following beneficial effects: This application proposes a lithium replenishment material comprising a composite structure formed by a core, a first coating layer, and a second coating layer. The core is made of a lithium, silicon, and oxygen-based compound, which can improve the cycle stability and high-temperature performance of the positive electrode. The first coating layer is a uniform coating formed of carbon material, which not only isolates external moisture and carbon dioxide but also improves electronic conductivity. The second coating layer is an incomplete coating formed of lithium silicon metal oxide, which is dotted and dispersed on the surface of the material, reducing residual alkali on the surface of the lithium replenishment material and providing a higher irreversible active lithium content. The lithium replenishment material with the above-mentioned composite structure not only provides lithium-ion supply during the delithiation process but also improves the electrochemical stability of the positive electrode active material (e.g., lithium cobalt oxide), helping to avoid unnecessary side reactions with the electrolyte. Simultaneously, this lithium replenishment material has a high specific capacity, effectively improving the energy density of lithium-ion batteries. Furthermore, the selection of carbon sources and different metals in this lithium replenishment material lowers the core decomposition potential, enabling the delithiation reaction to complete within the normal operating voltage range of lithium-ion batteries. Ultimately, by optimizing the design of the lithium replenishment material, this application significantly improves the overall performance of lithium-ion batteries, making them perform better in demanding applications. It not only exhibits good high-temperature storage and thermal performance but also maintains excellent high-temperature storage and high-temperature cycling performance at high voltages, demonstrating extremely broad application prospects in the field of rechargeable batteries.
[0023] In some embodiments, the first coating layer completely covers the surface of the core. The first coating layer is a uniform coating formed of carbon material, completely covering the core. This application utilizes carbon material as the first coating layer, uniformly covering the entire surface of the core. This coating layer not only isolates external moisture and carbon dioxide but also improves electronic conductivity.
[0024] In some implementations, the median granularity Dv of the kernel 50 The content of the first coating layer as a percentage of the mass fraction of the lithium replenishment material, W1, and the coating distribution density C of the second coating layer satisfy the following relationship: 3 ≤ C / Dv 50 ×W1≤9, where Dv 50 The unit is μm, the unit of W1 is %, and the unit of C is %.
[0025] In some implementations, the median granularity Dv of the kernel 50 The range is 0.1~3μm. For example, it can be 0.1μm, 0.5μm, 1.0μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, or within any two of the above values.
[0026] In some embodiments, the content of the first coating layer as a percentage of the mass fraction W1 of the lithium supplement material ranges from 0 to 10%. For example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or within any two of the above values.
[0027] In some embodiments, the distribution density C of the second coating layer ranges from 20% to 70%. Exemplarily, it can be 20%, 30%, 40%, 50%, 60%, 70%, or within any two of the aforementioned values. The distribution density is the area of the dotted coating on the particle surface divided by the total area of the particle. In this application, the distribution density C is the ratio of the area of the second coating layer material on the surface of the first coating layer to the total area of the first coating layer.
[0028] Conventional lithium-supplementing materials, due to their high lithium content, often require the addition of excessive lithium source during synthesis to achieve the desired crystal structure. However, this often results in excessive residual alkali, which can negatively impact high-temperature storage and thermal box performance during application. The lithium-supplementing material provided in this application, through the synergistic effect of its core, first coating layer, and second coating layer, reduces the probability of physical gelation during application, and when C / Dv... 50 When ×W1 satisfies the above relational constraints, the residual alkali of the lithium replenishment material is at its lowest, which can greatly improve the high-temperature storage and thermal box level of the entire cell system.
[0029] In some embodiments, lithium silicon oxide includes Li x Si y O z Where 0 < x < 10, 0 < y ≤ 5, 0 < z ≤ 12, and x, y, and z are all integers. The lithium replenishment material of this application uses a lithium, silicon, and oxygen-based compound as its core, which can effectively provide lithium ions and maintain relative stability during delithiation, thereby improving the cycle stability and high-temperature performance of the cathode.
[0030] In some implementations, lithium silicon oxide (Li x Si y O z The lithium silicon oxide includes at least one of lithium monosilicate, lithium disilicate, lithium trisilicate, lithium tetrasilicate, and lithium pentasilicate, but is not limited thereto. The lithium silicon oxide can be any combination of Li, Si, and O elements.
[0031] In some embodiments, the lithium silicon oxide includes Li8SiO6, Li4SiO4, Li2SiO3, Li6Si2O7, Li2Si2O5, Li2Si3O7, Li4Si3O8, Li4Si4O4, and Li2Si5O. 11 At least one of them, but not limited to.
[0032] Specifically, lithium silicate includes at least one of Li8SiO6, Li4SiO4, and Li2SiO3, but is not limited to these.
[0033] Specifically, lithium disilicate includes at least one of Li6Si2O7 and Li2Si2O5, but is not limited to this.
[0034] Specifically, lithium trisilicate includes at least one of Li2Si3O7 and Li4Si3O8, but is not limited to this.
[0035] Specifically, lithium tetrasilicate includes Li4Si4O4, but is not limited to this.
[0036] Specifically, lithium pentasilicate includes Li2Si5O 11 However, it is not limited to this.
[0037] In some embodiments, the material of the first coating layer includes a carbon (C) material, which includes at least one of bio-carbon, conductive carbon, graphene, and carbon nanotubes, but is not limited thereto. The carbon material used in this application is a carbon-containing organic or inorganic material, and its form is not limited in any way.
[0038] In some embodiments, the content of the first coating layer as a percentage of the mass fraction W1 of the lithium supplement material ranges from 0 to 10%. For example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or within any two of the above values.
[0039] In some specific embodiments of this application, the content of carbon material as a percentage of the mass fraction W1 of the lithium supplement material ranges from 0 to 10%. For example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or within any two of the above values.
[0040] In some embodiments, the material of the second coating layer includes lithium silicon metal oxide, which includes Li₂N. d Si (2-d) O4, wherein 0 < d ≤ 0.5, and N is selected from at least one of Na, Mg, and Al, but is not limited thereto.
[0041] In some embodiments, the material of the second coating layer is a lithium-silicon metal salt, including lithium magnesium silicate, lithium sodium silicate, or lithium aluminum silicate, but is not limited thereto.
[0042] In some embodiments, the content of the material in the second coating layer as a mass fraction W2 of the lithium supplement material ranges from 0 < W2 ≤ 2%. For example, W2 can be 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, or within any two of the above values.
[0043] In some specific embodiments of this application, lithium silicon metal oxide (Li2N) d Si (2-d) The content of O4 in the mass fraction W2 of the lithium supplement material is in the range of 0 < W2 ≤ 2%. Specifically, the content of lithium silicon metal oxide in the mass fraction W2 of the lithium supplement material can be 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, or any two of these values.
[0044] In some embodiments, the second coating layer at least partially covers the surface of the first coating layer, and the coating of the second coating layer is in the form of dot-like coating.
[0045] In this application, the second coating layer formed by lithium silicon metal oxide is a dotted coating, not completely covering the surface of the carbon material coating layer. This coating layer not only reduces residual alkali on the surface of the lithium replenishment material, but also provides a higher irreversible active lithium content.
[0046] This application uses carbon materials and lithium silicon metal oxides as coating materials to coat the core, which can enhance the conductivity and electrochemical stability of the core.
[0047] In one specific embodiment of this application, a lithium replenishment material is provided, the structure of which is Li x Si y O z -C@Li2N d Si (2-d) O4, 0 < x < 10, 0 < y ≤ 5, 0 < z ≤ 12, and x, y, and z are all integers, 0 < d ≤ 0.5, N is selected from at least one of Na, Mg, and Al; lithium supplementation materials include Li x Si y O z The core, the first coating layer formed by carbon materials, and Li2N d Si (2-d) The second coating layer is formed by O4, and the first coating layer is uniformly coated on the surface of the core, while the second coating layer is dotted on the surface of the first coating layer.
[0048] The lithium supplementary material Li provided in this application x Siy O z -C@Li2N d Si (2-d) O4, with its high specific capacity (approximately 600-620 mAh / g), can effectively improve the energy density of lithium-ion batteries. Compared to other active lithium sources, Li... x Si y O z -C@Li2N d Si (2-d) O4 exhibits better thermal stability and chemical inertness at high temperatures. Furthermore, Li... x Si y O z -C@Li2N d Si (2-d) O4 contains carbon sources (-C) and different metals (Li2N). d Si (2-d) The use of metallic N in O4 reduces the core Li x Si y O z The decomposition potential allows it to complete the delithiation reaction normally within the operating voltage range of lithium-ion batteries. Furthermore, this lithium replenishment material includes a lithium metal salt coating layer, Li₂N. d Si (2-d) O4, which is dispersed in a dot-like coating on the surface of the material, utilizes the core Li x Si y O z The residual alkali on the material surface forms a second coating layer, reducing the residual alkali in the lithium-supplementing material. Ultimately, this lithium-supplementing material... x Si y O z -C@Li2N d Si (2-d) O4 can significantly improve the overall performance of lithium-ion batteries, making them perform better in demanding applications. It not only has good high-temperature storage and thermal performance, but also maintains excellent high-temperature storage and high-temperature cycling performance under high voltage, making it extremely promising for applications in the field of rechargeable batteries.
[0049] In some implementations, kernel Li x Si y O z Median particle size Dv 50 The carbon content as a percentage of the mass fraction of the lithium-supplementing material, W1; and the second coating layer, Li2N. d Si (2-d) The density of states C of the O4 coating satisfies the relationship: 3≤C / Dv 50 ×W1≤9.
[0050] In some implementations, kernel Li x Si y O z Median particle size Dv 50 The range is 0.1~3μm.
[0051] In some embodiments, the carbon content of the lithium supplement material ranges from 0 to 10% of the mass fraction W1 of the lithium supplement material.
[0052] In some embodiments, the second coating layer Li2N d Si (2-d) The distribution state density C of O4 ranges from 20% to 70%. Distribution state density is the area of the coating formed by point-like particles on the particle surface divided by the total area of the particle. In this application, the distribution state density C is Li2N. d Si (2-d) The ratio of the area of O4 coating on the surface of carbon materials to the total area of the carbon materials.
[0053] The lithium replenishment material provided in this application, while ensuring the amount of lithium replenishment, can convert the residual lithium salt on the surface of the core material into a second coating layer, greatly reducing surface residual alkali and the probability of physical gelation during application. Furthermore, when C / Dv... 50 When ×W1 satisfies the above relational constraints, the residual alkali of the lithium replenishment material is at its lowest, which can greatly improve the high-temperature storage and thermal box level of the entire cell system.
[0054] In some specific embodiments of this application, the lithium supplementation material Li a Si b O c -C@Li2N d Si (2-d) In O4, Li a Si b O c Median particle size Dv 50 The content of carbon materials as a percentage of the mass fraction of lithium-supplementing materials, W1, and Li2N. d Si (2-d) The point-like coating density of states C of O4 satisfies the relationship: 3≤C / Dv 50 ×W1≤9. At this point, the lithium replenishment material exhibits the best high-temperature storage and thermal box performance in application.
[0055] This application also proposes a method for preparing the above-mentioned lithium supplementation material, characterized by comprising the following steps: Preparation of S100, carbon-coated lithium silicon oxide materials: Lithium carbonate, silicon dioxide, and carbon source are mixed evenly according to a predetermined mass fraction, and the evenly mixed powder is sintered once. After sintering, the powder is cooled naturally to obtain carbon-coated lithium silicon oxide material. S200, preparation of secondary coating layer: The metal oxide and carbon-coated lithium silicon oxide materials are remixed evenly, sintered a second time, and then cooled naturally. S300: After air jet milling and sieving, the powder is used to obtain lithium supplement material.
[0056] The method for preparing cathode lithium supplementation materials provided in this application employs a solid-state synthesis method, firstly preparing a carbon-coated lithium silicon oxide material (Li... x Si y O z The core material is coated with a -C material; then, the metal oxides (Al, Mg, Na sources) and the primary sintering material are remixed and homogenized, and a second sintering is performed followed by natural cooling to form Li2N. d Si (2-d) O4. This method is simple and easy to synthesize, and the resulting lithium-replenishing material has high specific capacity and low residual alkali.
[0057] <Cathode Materials> In a second aspect of this application, a positive electrode material is provided, comprising a positive electrode active material and the aforementioned lithium supplementation material; the positive electrode active material comprises lithium cobalt aluminum oxide.
[0058] In some embodiments, the mass ratio of lithium supplementation material in the cathode material is 0.1 to 0.5 wt%.
[0059] In some embodiments, lithium cobalt aluminum oxide includes LiCo (1-x-y) M x Al y O2, where 0 < x ≤ y ≤ 0.05, and M is selected from at least one of Mg, Ti, Zr, Co, Zr, Mn, Y, La, Sr, W, and Sc.
[0060] In some embodiments, the aluminum content in the cathode material accounts for W% of the mass fraction of the cathode material. A The range is 10,000 to 20,000 ppm. For example, it can be 10,000 ppm, 11,000 ppm, 12,000 ppm, 13,000 ppm, 14,000 ppm, 15,000 ppm, 16,000 ppm, 17,000 ppm, 18,000 ppm, 19,000 ppm, 20,000 ppm, or within the range of any two of the above values.
[0061] In some embodiments, the silicon content in the cathode material accounts for W% of the mass fraction of the cathode material. BThe range is 150 to 950 ppm. For example, it can be 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 550 ppm, 600 ppm, 650 ppm, 700 ppm, 750 ppm, 800 ppm, 850 ppm, 900 ppm, 950 ppm, or within the range of any two of the above values.
[0062] In some embodiments, the aluminum content in the cathode material accounts for W% of the mass fraction of the cathode material. A The content of silicon element as a percentage of the mass fraction of the cathode material, W B The ratio satisfies the following relationship: 16 ≤ W A / W B ≤66.6.
[0063] In some embodiments, the aluminum content in the cathode material accounts for W% of the mass fraction of the cathode material. A The range is 10,000~20,000 ppm, and the silicon content accounts for W of the mass fraction of the cathode material. B The range is 150~500 ppm, and the aluminum content accounts for W of the mass fraction of the cathode material. A The content of silicon as a percentage of the mass of the cathode material (W) B The ratio satisfies the following relationship: 16 ≤ W A / W B ≤66.6.
[0064] In high voltage lithium cobalt aluminum oxide (LiCo) (1-x-y) M x Al y (O2) Increasing the charging cutoff voltage and gradually increasing the Al content leads to the formation of more Al-O bonds, which can stabilize the oxygen layer structure and reduce cobalt dissolution. After the lithium-replenishing material completes the first delithiation reaction, the active Si element tends to coordinate with oxygen in tetrahedral configurations, causing partial shrinkage of the crystal structure. This counteracts the large octahedral expansion effect of excessively high Al content, maintaining the LiCo... (1-x-y) M x Al y The O2 layered structure achieves overall strain equilibrium and exhibits greater stability at high voltages (≥4.55V), maintaining cycle stability under high charge cutoff voltages. When W A / W B When the above constraints are met, the excessive Al elements deposited on LiCo under high voltage can be offset. (1-x-y) M x Al yThe lattice expansion effect formed by O2 and the local contraction effect brought by Si atoms better stabilize the strain balance of the host material. After completing the first cycle, this lithium replenishment material can obtain a more stable layered structure under high voltage, improving the high-temperature performance of the entire cell system and giving it superior high-temperature storage and high-temperature cycling performance.
[0065] In some embodiments, the positive electrode active material includes an aluminum-containing lithium cobalt oxide with the chemical formula: LiCo (1-x-y) M x Al y O2, 0 < x ≤ y ≤ 0.05, M is selected from at least one of Mg, Ti, Zr, Co, Zr, Mn, Y, La, Sr, W, Sc.
[0066] <Positive Electrode Tablets> A third aspect of this application provides a positive electrode sheet, including a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, the positive active material layer including the aforementioned positive electrode material.
[0067] In some embodiments, the positive electrode active material layer further includes a positive electrode binder and a positive electrode conductive agent.
[0068] In some embodiments, the mass percentage of each component in the positive electrode active material layer, taking the lithium replenishing material, positive electrode active material, conductive agent, and binder as a whole, is as follows: positive electrode active material 95.5~98.9%, conductive agent 0.5~2%, binder 0.5~2%, and lithium replenishing material 0.1~0.5%.
[0069] In some embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), poly(vinylidene fluoride)-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, polyacrylic acid, polyacrylonitrile, polyimide, polyurethane, polyvinyl butyral, polyvinylpyrrolidone (PVP), acrylic acid-acrylonitrile-acrylamide copolymer, and acrylic acid-acrylonitrile-acrylate copolymer. The positive electrode binder of this application is not limited to the above materials, but also includes other materials that can be used as battery positive electrode binders. In some embodiments, the positive electrode conductive agent may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon nanotubes, carbon nanotubes, activated carbon, and mesoporous carbon. The positive electrode conductive agent in this application is not limited to the above materials, but also includes other materials that can be used as positive electrode conductive agents in batteries.
[0070] In some embodiments, the positive current collector is a metal foil or a composite current collector. In some embodiments, the metal foil is an aluminum foil. The composite current collector may include a metal foil substrate and a conductive layer disposed on at least one side of the metal foil substrate.
[0071] In some embodiments, the conductive layer may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fiber, carbon nanofiber, graphitized carbon sheet, carbon tube, carbon nanotube, activated carbon, and mesoporous carbon. In some embodiments, the preparation method of the positive electrode sheet includes the following steps: thoroughly mixing the positive electrode material, conductive agent, binder, and solvent according to a mass ratio, coating the mixture onto the positive electrode current collector, and then drying, cold pressing, and slitting to obtain the positive electrode sheet. The preparation method of the positive electrode sheet can adopt conventional methods in the industry, and this application does not limit it.
[0072] <Battery Cell> A fourth aspect of this application also proposes a battery cell comprising a negative electrode and the aforementioned positive electrode.
[0073] Since the battery cell adopts all the technical solutions of the positive electrode sheet in the above embodiments, it possesses at least all the beneficial effects brought about by the technical solutions in the above embodiments. That is, it significantly improves the overall performance of the lithium-ion battery, making it perform better in demanding application scenarios. It not only has good high-temperature storage and thermal performance, but also maintains excellent high-temperature storage and high-temperature cycling performance at high voltage, showing extremely broad application prospects in the field of rechargeable batteries.
[0074] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector.
[0075] In some embodiments, the negative current collector is a metal foil or a composite current collector. In some embodiments, the metal foil is a copper foil. The composite current collector may include a metal foil substrate and a conductive layer disposed on at least one side of the metal foil substrate.
[0076] In some embodiments, the conductive layer may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fiber, carbon nanofiber, graphitized carbon sheet, carbon tube, carbon nanotube, activated carbon, and mesoporous carbon.
[0077] In some embodiments, the negative electrode active material layer includes a negative electrode active material, a negative electrode binder, and a negative electrode binder conductive agent.
[0078] In some embodiments, the negative electrode active material may include natural graphite particles, synthetic graphite particles, hard carbon, soft carbon, mesophase carbon microspheres (MCMB), Sn, SnO2, SnO, Li4Ti5O 12The negative electrode active material is selected from at least one of LTO, Si materials, silicon-carbon (Si-C) composite materials, silicon-nitrogen (Si-N) composite materials, and silicon-oxygen (Si-O) composite materials. The negative electrode active material of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as negative electrode active materials for batteries.
[0079] In some embodiments, the negative electrode binder may include at least one of polyacrylic acid, polymethacrylic acid, polyacrylate, polymethacrylate, polyacrylamide, styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylic acid-acrylonitrile-acrylamide copolymer, acrylic acid-acrylonitrile-acrylate copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acryloyl rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyvinyl alcohol, polyvinyl acetate, polyepoxychloropropane, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, carboxymethyl chitosan, polyester, polyamide, polyether, polyimide, polycarboxylic acid ester, polycarboxylic acid, polyurethane, alginate, fluorinated polymer, chlorinated polymer, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropylene. The negative electrode binder of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as battery negative electrode binders. In some embodiments, the negative electrode conductive agent may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon nanotubes, carbon nanotubes, activated carbon, and mesoporous carbon. The negative electrode conductive agent of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as battery negative electrode conductive agents.
[0080] In some embodiments, a method for preparing the above-mentioned negative electrode sheet is also provided, including the steps of: thoroughly mixing the negative electrode active material, conductive agent, and binder according to a mass ratio, coating the mixture onto the negative electrode current collector, and then drying, cold pressing, and slitting to obtain the negative electrode sheet. The preparation method of the negative electrode sheet can adopt conventional methods in the industry, and this application does not limit it.
[0081] <Electrochemical Device> A fifth aspect of this application also proposes an electrochemical device comprising the aforementioned battery cell.
[0082] The electrochemical device provided in this application includes any device in which an electrochemical reaction occurs to convert chemical energy into electrical energy and vice versa. Specific, non-limiting examples include all types of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors. In particular, the electrochemical device is a lithium secondary battery, including lithium metal secondary batteries, lithium-ion secondary batteries, lithium polymer secondary batteries, or lithium-ion polymer secondary batteries.
[0083] In some embodiments, the electrochemical device includes a lithium-ion battery.
[0084] In some embodiments, the electrochemical device includes a positive electrode, a negative electrode, an electrolyte, and a separator located between the positive and negative electrodes.
[0085] The separator separates the negative and positive electrodes and provides a pathway for lithium-ion migration. The use of the separator is not particularly limited, as long as it is a separator commonly used in lithium-ion secondary batteries. In particular, separators with low resistance to electrolyte ion movement and excellent electrolyte permeability are preferred. Specifically, porous polymer membranes can be used, such as porous polymer membranes formed from polyolefin-based polymers (e.g., ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, ethylene / methacrylate copolymers, etc.) or laminated structures with two or more layers. Alternatively, nonwoven fabrics formed from conventional porous nonwoven fabrics (e.g., glass fibers with high melting points, polyethylene terephthalate fibers, etc.) can be used. Furthermore, coated separators containing ceramic components or polymer materials to ensure heat resistance or mechanical strength can be used, and can optionally be used as single-layer or multi-layer structures. Generally, a diaphragm includes a substrate and a coating applied to the surface of the substrate. In some embodiments, the porous substrate is, but is not limited to, at least one of polyolefins, polyesters, polyacetals, polyamides, polyethylene terephthalate, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, polyacrylonitrile, polyvinylidene fluoride, polyoxymethylene, polyoxymethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, polysulfone, and polymethyl methacrylate. Some non-limiting examples of polyolefins include at least one of polyethylene (PE), ultra-high molecular weight polyethylene (UHMWPE), high-density polyethylene (HDPE), polypropylene (PP), polyethylene-polypropylene copolymer (PE-PP), and polyethylene-polypropylene-polyethylene copolymer. In some embodiments, the coating is disposed on one side of the substrate. In some embodiments, the coating is disposed on both sides of the substrate.
[0086] In some embodiments, the coating includes inorganic fillers and adhesives.
[0087] In some embodiments, the inorganic filler comprises Al2O3, SiO2, TiO2, ZrO2, Mg(OH)2, MgO, SnO2, CaCO3, BaSO4, TiN, AlN, Na2O.mTiO2, K2O.nTiO2, BaO x MTiO3 and combinations thereof, wherein m is 3 or 6, n is 1, 2, 4, 6 or 8, x is 1 or 2, and M is Ba, Sr or Ca. The inorganic filler may be spherical, plate-like, disc-like, needle-like, cylindrical, irregular or other known particle shapes.
[0088] In some embodiments, the inorganic filler includes one or more of alumina, hydrated alumina, boehmite, magnesium hydroxide, magnesium oxide, titanium dioxide, zirconium oxide, and barium sulfate. In some implementations, the binder is a water-soluble polymer.
[0089] In some implementations, the water-soluble polymer is a homopolymer or copolymer. In some embodiments, the water-soluble binder includes at least one of polyamide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, polymethacrylic acid, polymethacrylate, polyvinyl alcohol, polyvinyl acetate, polyacrylamide, cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, carboxymethyl cellulose, cyanoethyl cellulose, nitrile rubber (NBR), styrene-butadiene rubber (SBR), and latex.
[0090] In some implementations, the binder is an oil-soluble polymer. In some embodiments, non-limiting examples of oil-soluble polymers include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyester, polyether, polyvinyl compounds, polyolefins, rubber, polyvinylpyrrolidone, polystyrene, nitrile rubber (NBR), styrene-butadiene rubber (SBR), latex, acrylonitrile-styrene-butadiene copolymer, halogenated polymers, fluorinated polymers, chlorinated polymers, unsaturated polymers, conjugated diene polymers, and combinations thereof.
[0091] In some embodiments, the electrolyte may include at least one of a gel electrolyte, a solid electrolyte, and a liquid electrolyte. In some embodiments, the liquid electrolyte may include a non-aqueous solvent and a lithium salt.
[0092] In some embodiments, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. In some embodiments, the non-aqueous solvent may be at least one of carbonate compounds, carboxylic acid ester compounds, and ether compounds. In some embodiments, the carbonate compound may include at least one of chain carbonate compounds, cyclic carbonate compounds, and fluorocarbonate compounds. In some embodiments, the chain carbonate compound may include diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), and combinations thereof. In some embodiments, the cyclic carbonate compound may include ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), vinyl ethylene carbonate (VEC), and combinations thereof. In some embodiments, the fluorocarbonate compound may include at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate. In some embodiments, the carboxylic acid ester compound may include at least one of methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid lactone, valerate lactone, mevalonate lactone, caprolactone, and methyl formate. In some embodiments, the ether compound may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof. In some embodiments, the non-aqueous solvent may also include at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters.
[0093] <Electronic Devices> In a sixth aspect, the present invention provides an electronic device comprising the electrochemical device described above.
[0094] The electronic device described in this application is not particularly limited and may be any electronic device known in the prior art. The application of the electrochemical device in this application is not particularly limited, and it can be used in any electronic device known in the prior art. Some embodiments of this application include electronic devices such as mobile phones, smartphones, laptops, tablets, wearable devices, smartwatches, smart bracelets, smart glasses, power banks, televisions, game consoles, game controllers, digital cameras, smart speakers, headphones, keyboards, mice, monitors, drones, audio equipment, home appliances, toys, power tools, automobiles, motorcycles, electric bicycles, bicycles, robots, robot dogs, industrial robots, and android robots.
[0095] Unless otherwise specified in the following examples, the techniques or conditions described in the literature in this field or in accordance with the product instructions shall apply. All reagents or instruments without a specified manufacturer are commercially available conventional products.
[0096] Example 1 A lithium-ion secondary battery (1) Preparation of lithium supplementation materials a. Weigh lithium carbonate and silicon dioxide at a molar ratio of 2:1 and mix them evenly to obtain mixed crude material 1. (The molar ratio is not shown in other examples; the elemental molar ratio of the final product is used for addition, and the molar ratio of each raw material is added according to the stoichiometric coefficient of the final compound.) b. Continue mixing the mixed coarse material 1 from a with the carbon source (glucose), with the carbon source accounting for 5% of the total mass fraction, until no visible white spots are observed.
[0097] c. Sinter the powder mixed evenly in step b once. To prevent material oxidation or moisture absorption, use an inert gas (nitrogen). Hold at 800℃ for 5 hours and then allow to cool naturally.
[0098] d. Mix the powder obtained in c with magnesium oxide at a mass ratio of 1:0.003 (as above, the proportions are not shown in other examples, but are added according to the elemental proportions of the final product. The proportions of each raw material can be deduced from the stoichiometric coefficients of the final compound, which will not be repeated here). After holding the mixture at 450°C with an inert gas (nitrogen) for 3 hours, allow it to cool naturally.
[0099] e. The powder obtained in step d is subjected to air jet milling and sieved through a 300-mesh sieve to complete the preparation of the lithium replenishment material.
[0100] The chemical formula of this lithium replenishment material is Li4SiO4-C@Li2MgSiO4, with a core of Li4SiO4 and a coating layer of C@Li2MgSiO4.
[0101] (2) Preparation of positive electrode active material a. Weigh cobalt tetroxide and lithium carbonate at a molar ratio of lithium:cobalt = 1:1.02 and mix them evenly to obtain mixture 1 (no white particles visible to the naked eye).
[0102] b. The mixture 1 obtained in a is sintered once in an air atmosphere at a sintering temperature of 1050℃ for 6 hours and then cooled naturally.
[0103] c. The sintered material obtained in step b is mixed evenly with an Al source (aluminum hydroxide) and a Mg source (magnesium hydroxide) to obtain a sintered mixture. The Al element content is controlled to be 20,000 ppm and the Mg element content to be 5,000 ppm. The sintered mixture is then subjected to secondary sintering in an air atmosphere at a sintering temperature of 650℃ for 2 hours. After natural cooling, the resulting material has the chemical formula LiCo. 0.975 Mg 0.005 Al 0.02 O2 is the positive electrode active material.
[0104] (3) Preparation of positive electrode The positive electrode active material (LiCo) 0.975 Mg 0.005 Al 0.02 O2), lithium supplement material Li4SiO4-C@Li2MgSiO4, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed thoroughly in an N-methylpyrrolidone solvent system at a mass ratio of 97:1:0.6:1.4. The mixture is then coated onto both sides of the positive electrode current collector Al foil. The positive electrode sheet is obtained through processes such as drying, cold pressing, slitting, and cutting.
[0105] Among them, the mass fraction of Al element in the cathode material is W A The mass fraction of Si element W in the cathode material is approximately 20,000 ppm. B Approximately 430 ppm, W A / W B =46.51. Median particle size Dv of the core of the lithium replenishment material. 50 The thickness is 1.1 μm, the carbon coating content W1 is 6%, the coating state density C of the second coating layer is 25%, and the C / Dv ratio is 1.1 μm. 50 ×W1=3.79.
[0106] Among them, W AThe amount of Al source added is controlled by adjusting the sintering process of the positive electrode active material (high aluminum doped lithium cobalt oxide), as shown in this embodiment, W. A Approximately 20,000 ppm, meaning that 20,000 ppm of aluminum source is added during the second sintering process; W B This can be controlled by adjusting the amount of silicon added; the above applies to W. A W B The method of regulation is not limited, and conventional methods in the field can be reasonably applied as long as they can achieve the purpose of this application. The final amount added shall be based on the test after the cell is disassembled.
[0107] Median particle size Dv of the core of lithium replenishment material 50 This is achieved by adjusting the airflow pulverization time, and the adjustment method is not limited. Conventional methods in the field can be reasonably applied as long as they can achieve the purpose of this application. The final particle size is determined by testing after the battery cell is disassembled.
[0108] The amount of carbon coating can be controlled by the proportion of coating material and process parameters, and the control method is not limited. Conventional methods in the field can be reasonably applied as long as they can achieve the purpose of this application. The final amount of carbon coating is determined by testing after the battery cell is disassembled.
[0109] The density of the second coating layer can be controlled by the proportion of coating material and process parameters, and the control method is not limited. Conventional methods in the field can be reasonably applied as long as they can achieve the purpose of this application. The final density of the coating layer is determined by the test after the cell is disassembled.
[0110] The methods for adjusting the above parameters are well known in the art. Those skilled in the art can select a reasonable adjustment method based on the final parameters. The following embodiments will not be described in detail.
[0111] (4) Preparation of negative electrode The negative electrode active material graphite, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are thoroughly mixed in a deionized water solvent system at a mass ratio of 96:1:1.5:1.5. The mixture is then coated onto the negative electrode current collector Cu foil, dried, cold-pressed, and slit to obtain the negative electrode sheet.
[0112] (5) Preparation of the separating membrane Polyethylene (PE) porous polymer film is used as the separator.
[0113] (6) Preparation of electrolyte A solution prepared by mixing lithium salt LiPF6 with a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): ethylene carbonate (VC)) in a mass ratio of 20:30:20:28:2, with a mass ratio of 8:92) is used as the electrolyte for lithium-ion secondary batteries.
[0114] (7) Preparation of lithium-ion secondary batteries The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes for safety isolation. The electrodes are then wound to form an electrode assembly. This assembly is placed in a packaging shell, infused with electrolyte, and sealed to obtain a lithium-ion secondary battery. In this battery, the N / P ratio between the negative and positive electrodes is 1.09.
[0115] Example 2 The difference from Example 1 is that the core of the lithium replenishing material is different, which is Li2SiO3, and the lithium replenishing material is Li2SiO3-C@Li2MgSiO4.
[0116] The rest is the same as in Example 1, and will not be repeated here.
[0117] Example 3 The difference from Example 1 is that the core of the lithium replenishing material is different, which is Li8SiO6, and the lithium replenishing material is Li8SiO6-C@Li2MgSiO4.
[0118] The rest is the same as in Example 1, and will not be repeated here.
[0119] Example 4 The difference from Example 1 is that the core of the lithium replenishing material is different, which is Li6Si2O7, and the lithium replenishing material is Li6Si2O7-C@Li2MgSiO4.
[0120] The rest is the same as in Example 1, and will not be repeated here.
[0121] Example 5 The difference from Example 1 is that the core of the lithium replenishing material is different, which is Li2Si2O5, and the lithium replenishing material is Li2Si2O5-C@Li2MgSiO4.
[0122] The rest is the same as in Example 1, and will not be repeated here.
[0123] Example 6 The difference from Example 1 is that the core of the lithium replenishing material is different, which is Li2Si3O7, and the lithium replenishing material is Li2Si3O7-C@Li2MgSiO4.
[0124] The rest is the same as in Example 1, and will not be repeated here.
[0125] Example 7 The difference from Example 1 is that the core of the lithium replenishing material is different, which is Li4Si3O8, and the lithium replenishing material is Li4Si3O8-C@Li2MgSiO4.
[0126] The rest is the same as in Example 1, and will not be repeated here.
[0127] Example 8 The difference from Example 1 is that the core of the lithium replenishing material is different, which is Li4Si4O4, and the lithium replenishing material is Li4Si4O4-C@Li2MgSiO4.
[0128] The rest is the same as in Example 1, and will not be repeated here.
[0129] Example 9 The difference from Example 1 is that the core of the lithium-supplementing material is different, being Li2Si5O. 11 The lithium supplement material is Li2Si5O 11 -C@ Li2MgSiO4.
[0130] The rest is the same as in Example 1, and will not be repeated here.
[0131] Example 10 The difference from Example 1 is that the Al element content W in the cathode material is... A The Si element content in the cathode material is approximately 18,000 ppm (W). B Approximately 950 ppm, W A / W B =18.95.
[0132] The rest is the same as in Example 1, and will not be repeated here.
[0133] Example 11 The difference from Example 1 is that the core of the lithium replenishment material is different; it is Li2Si2O5, and the lithium replenishment material is Li2Si2O5-C@Li2MgSiO4. The Al content W in the cathode material is... A The Si element content in the cathode material is approximately 17,000 ppm (W). B Approximately 280 ppm, W A / W B =60.71.
[0134] The rest is the same as in Example 1, and will not be repeated here.
[0135] Example 12 The difference from Example 1 is that the core of the lithium replenishment material is different; it is Li4Si3O8, while the lithium replenishment material is Li4Si3O8-C@Li2MgSiO4. The Al content W in the cathode material is also different.A The Si element content in the cathode material is approximately 16,000 ppm (W). B Approximately 770 ppm, W A / W B =20.78.
[0136] The rest is the same as in Example 1, and will not be repeated here.
[0137] Example 13 The difference from Example 1 is that the median particle size Dv of the lithium replenishment material's core is... 50 The thickness is 0.2 μm, the carbon coating content W1 is 10%, the density of states of the second coating layer C is 15%, and the C / Dv ratio is 0.2 μm. 50 ×W1=7.5.
[0138] The rest is the same as in Example 1, and will not be repeated here.
[0139] Example 14 The difference from Example 1 is that the core of the lithium replenishment material is different; it is Li2Si2O5, while the lithium replenishment material is Li2Si2O5-C@Li2MgSiO4. The median particle size Dv of the core of the lithium replenishment material is... 50 The thickness is 2.6 μm, the carbon coating content W1 is 6%, the second coating layer coating state density C is 50%, and the C / Dv ratio is 2.6 μm. 50 ×W1=3.2.
[0140] The rest is the same as in Example 1, and will not be repeated here.
[0141] Example 15 The difference from Example 1 is that the core of the lithium replenishment material is different; it is Li4Si3O8, while the lithium replenishment material is Li4Si3O8-C@Li2MgSiO4. The median particle size Dv of the core of the lithium replenishment material is... 50 The thickness is 1.9 μm, the carbon coating content W1 is 5%, the coating state density C of the second coating layer is 40%, and the C / Dv ratio is 1.9 μm. 50 ×W1=4.2.
[0142] The rest is the same as in Example 1, and will not be repeated here.
[0143] Example 16 The difference from Example 1 is that the second coating layer is different, which is lithium aluminum silicate, and the lithium replenishment material is Li4SiO4-C@Li2AlSiO4.
[0144] The rest is the same as in Example 1, and will not be repeated here.
[0145] Example 17 The difference from Example 1 is that the second coating layer is different, which is lithium sodium silicate, and the lithium replenishment material is Li4SiO4-C@Li2NaSiO4.
[0146] The rest is the same as in Example 1, and will not be repeated here.
[0147] Example 18 The difference from Example 1 is that the Al element content W in the cathode material is... A The Si element content in the cathode material is approximately 10,000 ppm (W). B Approximately 620 ppm, W A / W B =16.13.
[0148] The rest is the same as in Example 1, and will not be repeated here.
[0149] Example 19 The difference from Example 1 is that the Al element content W in the cathode material is... A The Si element content in the cathode material is approximately 17,000 ppm (W). B Approximately 250 ppm, W A / W B =62.87.
[0150] The rest is the same as in Example 1, and will not be repeated here.
[0151] Example 20 The difference from Example 1 is that the median particle size Dv of the lithium replenishment material's core is... 50 The thickness is 2.7 μm, the carbon coating content W1 is 6%, the coating state density C of the second coating layer is 50%, and the C / Dv ratio is 2.7 μm. 50 ×W1=3.08.
[0152] The rest is the same as in Example 1, and will not be repeated here.
[0153] Example 21 The difference from Example 1 is that the median particle size Dv of the lithium replenishment material's core is... 50 The thickness is 0.28 μm, the carbon coating content W1 is 8%, the density of states of the second coating layer C is 20%, and the C / Dv ratio is 0.28 μm. 50 ×W1=8.9.
[0154] The rest is the same as in Example 1, and will not be repeated here.
[0155] Example 22 The difference from Example 1 is that the Al element content W in the cathode material is... A The Si element content in the cathode material is approximately 13,000 ppm (W). B Approximately 870 ppm, WA / W B =14.94.
[0156] The rest is the same as in Example 1, and will not be repeated here.
[0157] Example 23 The difference from Example 1 is that the core of the lithium replenishment material is different; it is Li2Si2O5, and the lithium replenishment material is Li2Si2O5-C@Li2MgSiO4. The Al content W in the cathode material is... A The Si element content in the cathode material is approximately 18,000 ppm (W). B Approximately 240 ppm, W A / W B =75.
[0158] The rest is the same as in Example 1, and will not be repeated here.
[0159] Example 24 The difference from Example 1 is that the core of the lithium replenishment material is different; it is Li4Si3O8, while the lithium replenishment material is Li4Si3O8-C@Li2MgSiO4. The Al content W in the cathode material is also different. A The Si element content in the cathode material is approximately 14,000 ppm (W). B Approximately 970 ppm, W A / W B =14.43.
[0160] The rest is the same as in Example 1, and will not be repeated here.
[0161] Example 25 The difference from Example 1 is that the median particle size Dv of the lithium replenishment material's core is... 50 The thickness is 2.6 μm, the carbon coating content W1 is 10%, the second coating layer coating state density C is 10%, and the C / Dv ratio is 2.6 μm. 50 ×W1=0.38.
[0162] The rest is the same as in Example 1, and will not be repeated here.
[0163] Example 26 The difference from Example 1 is that the core of the lithium replenishment material is different; it is Li2Si2O5, while the lithium replenishment material is Li2Si2O5-C@Li2MgSiO4. The median particle size Dv of the core of the lithium replenishment material is... 50 The thickness is 0.3 μm, the carbon coating content W1 is 9%, the coating state density C of the second coating layer is 30%, and the C / Dv ratio is 0.3 μm. 50 ×W1=11.1.
[0164] The rest is the same as in Example 1, and will not be repeated here.
[0165] Example 27 The difference from Example 1 is that the core of the lithium replenishment material is different; it is Li4Si3O8, while the lithium replenishment material is Li4Si3O8-C@Li2MgSiO4. The median particle size Dv of the core of the lithium replenishment material is... 50 The thickness is 1.4 μm, the carbon coating content W1 is 20%, the second coating layer coating state density C is 20%, and the C / Dv ratio is 1.4 μm. 50 ×W1=0.71.
[0166] The rest is the same as in Example 1, and will not be repeated here.
[0167] Example 28 The difference from Example 1 is that the Al element content W in the cathode material is... A The Si element content in the cathode material is approximately 13,000 ppm (W). B Approximately 870 ppm, W A / W B =14.94. Median particle size Dv of the lithium replenishment material core. 50 The thickness is 2.6 μm, the carbon coating content W1 is 10%, the second coating layer coating state density C is 10%, and the C / Dv ratio is 2.6 μm. 50 ×W1=0.38.
[0168] The rest is the same as in Example 1, and will not be repeated here.
[0169] Example 29 The difference from Example 1 is that the Al element content W in the cathode material is... A The Si element content in the cathode material is approximately 20,000 ppm. B Approximately 240 ppm, W A / W B =83.33. The median particle size Dv of the lithium replenishment material's core. 50 The thickness is 2.6 μm, the carbon coating content W1 is 10%, the second coating layer coating state density C is 10%, and the C / Dv ratio is 2.6 μm. 50 ×W1=0.38.
[0170] The rest is the same as in Example 1, and will not be repeated here.
[0171] Example 30 The difference from Example 1 is that the Al element content W in the cathode material is... A The Si element content in the cathode material is approximately 14,000 ppm (W). B Approximately 970 ppm, W A / W B =14.43. The median particle size Dv of the lithium replenishment material's core. 50The thickness is 1.4 μm, the carbon coating content W1 is 20%, the second coating layer coating state density C is 20%, and the C / Dv ratio is 1.4 μm. 50 ×W1=0.71.
[0172] The rest is the same as in Example 1, and will not be repeated here.
[0173] Example 31 The difference from Example 1 is that the Al element content W in the cathode material is... A The Si element content in the cathode material is approximately 19,000 ppm (W). B Approximately 270 ppm, W A / W B =70.37. Median particle size Dv of the lithium replenishment material core. 50 The thickness is 0.2 μm, the carbon coating content W1 is 9%, the coating state density C of the second coating layer is 30%, and the C / Dv ratio is 0.2 μm. 50 ×W1=16.67.
[0174] The rest is the same as in Example 1, and will not be repeated here.
[0175] Comparative Example 1 The difference from Example 1 is that the lithium replenishment material is uncoated.
[0176] The rest is the same as in Example 1, and will not be repeated here.
[0177] Comparative Example 2 The difference from Example 1 is that the core of the lithium replenishing material is different, which is Li2Si2O5, and the lithium replenishing material is uncoated.
[0178] The rest is the same as in Example 1, and will not be repeated here.
[0179] Comparative Example 3 The difference from Example 1 is that the core of the lithium replenishing material is different, which is Li4Si3O8, and the lithium replenishing material is uncoated.
[0180] The rest is the same as in Example 1, and will not be repeated here.
[0181] Comparative Example 4 The difference from Example 1 is that the lithium supplement material is only coated with carbon material.
[0182] The rest is the same as in Example 1, and will not be repeated here.
[0183] Comparative Example 5 The difference from Example 1 is that the lithium replenishment material is only coated with lithium magnesium silicate.
[0184] The rest is the same as in Example 1, and will not be repeated here.
[0185] The materials and parameters of Examples 1-31 and Comparative Examples 1-5 are shown in Table 1: Table 1
[0186] In this context, " / " indicates that this data is not available.
[0187] Performance testing The performance of the batteries prepared in Examples 1-31 and Comparative Examples 1-5 was tested respectively, and the test methods are as follows: High-temperature storage at 85℃ for 8 hours: Measure the half-cell thickness D1. After fully charging the cell with constant current and constant voltage, immediately place it in an 85℃ constant temperature chamber for 8 hours. After removing it from the chamber, place it at room temperature for 3 minutes and immediately measure the cell thickness D2. The expansion rate is equal to (D2-D1) / D1.
[0188] Hot chamber temperature test: Fully charge the battery cells at room temperature, place the fully charged cells inside the hot chamber, control the temperature rise of the chamber and maintain it at ±2℃ for 30 minutes. If the batch of battery cells does not catch fire or explode within 30 minutes, it is considered to have passed the hot chamber test.
[0189] High-temperature cycling is performed using a conventional step-filling system: 1C equals 8000mAh. The following measurements were taken initially at 45℃, measuring the half-cell thickness D0 in the shipped state.
[0190] The initial constant current charge is 2.4C, and the cutoff voltage is 4.2V.
[0191] 1.8C constant current charging cutoff voltage 4.25V.
[0192] 1.5C constant current charging cutoff voltage 4.35V.
[0193] 1.2C constant current charging cutoff voltage 4.45V.
[0194] 0.7C constant current and constant voltage charging voltage upper limit 4.55V, cut-off current 0.02C.
[0195] Let it stand for 1 minute.
[0196] The 0.7C constant current discharge has a cutoff voltage of 2.8V. The initial discharge capacity is denoted as C0.
[0197] The discharge capacity at 400cls is denoted as C1, and the full charge thickness at 400cls is denoted as D1.
[0198] Wherein, the high-temperature 400cls retention rate = C1 / C0, and the high-temperature 400cls expansion rate = D1 / D0-1 The test data is shown in Table 2: Table 2
[0199] As can be seen from the above results, by optimizing the design of the lithium replenishment material, this application can significantly improve the overall performance of lithium-ion batteries, making them perform better in demanding application scenarios. They not only have good high-temperature storage and thermal box performance, but also maintain excellent high-temperature storage and high-temperature cycling performance under high voltage.
[0200] The embodiments described above are merely examples of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of this application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these modifications and improvements all fall within the protection scope of this application.
Claims
1. A lithium supplementation material, characterized in that, The lithium replenishment material includes a core, a first coating layer, and a second coating layer. The first coating layer completely covers the surface of the core, and the second coating layer partially covers the surface of the first coating layer. The core comprises lithium silicon oxide; The first coating layer comprises a carbon material; The second coating layer comprises lithium silicon metal oxide; The second coating layer is dotted on the surface of the first coating layer.
2. The lithium replenishment material according to claim 1, characterized in that, The median particle size Dv of the kernel 50 The content of the first coating layer as a percentage of the mass fraction W1 of the lithium replenishment material, and the coating distribution density C of the second coating layer satisfy the following relationship: 3 ≤ C / Dv 50 ×W1≤9; Among them, Dv 50 The unit is μm, the unit of W1 is %, and the unit of C is %.
3. The lithium replenishment material according to claim 1 or 2, characterized in that, Including at least one of the following (a1) to (a9): (a1) The lithium silicon oxide includes Li x Si y O z Where 0 < x < 10, 0 < y ≤ 5, 0 < z ≤ 12, and x, y, and z are all integers; (a2) When (a1) is included, the lithium silicon oxide includes at least one of lithium monosilicate, lithium disilicate, lithium trisilicate, lithium tetrasilicate, and lithium pentasilicate; (a3) When (a2) is included, the lithium silicon oxide includes Li8SiO6, Li4SiO4, Li2SiO3, Li6Si2O7, Li2Si2O5, Li2Si3O7, Li4Si3O8, Li4Si4O4, and Li2Si5O. 11 At least one of them; (a4) The median particle size Dv of the kernel 50 The range is 0.1~3μm; (a5) The carbon material includes at least one of biocarbon, conductive carbon, graphene, and carbon nanotubes; (a6) The content of the first coating layer as a percentage of the mass fraction W1 of the lithium replenishment material is in the range of 0 < W1 ≤ 10%; (a7) The lithium silicon metal oxide includes Li2N d Si (2-d) O4, wherein 0 < d ≤ 0.5, and N is selected from at least one of Na, Mg, and Al; (a8) The content of the second coating layer as a percentage of the mass fraction W2 of the lithium supplementation material is in the range of 0 < W2 ≤ 2%; (a9) The coating distribution density C of the second coating layer is in the range of 20~70%.
4. A positive electrode material, characterized in that, Includes positive electrode active material and lithium replenishment material as described in any one of claims 1-3; The positive electrode active material includes lithium cobalt aluminum oxide.
5. The positive electrode material according to claim 4, characterized in that, Including at least one of (b1) to (b4): (b1) The lithium cobalt aluminum oxide includes LiCo (1-x-y) M x Al y O2, where 0 < x ≤ y ≤ 0.05, and M is selected from at least one of Mg, Ti, Zr, Co, Zr, Mn, Y, La, Sr, W, and Sc; (b2) In the cathode material, the content of aluminum element accounts for W of the mass fraction of the cathode material. A The range is 10,000 to 20,000 ppm; (b3) In the cathode material, the content of silicon element accounts for W of the mass fraction of the cathode material. B The range is 150~950ppm; (b4) In the cathode material, the content of aluminum element accounts for W of the mass fraction of the cathode material. A The content of silicon element as a percentage of the mass fraction of the cathode material, W B The ratio satisfies the following relationship: 16 ≤ W A / W B ≤66.
6.
6. A positive electrode plate, characterized in that, It includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes the positive electrode material as described in any one of claims 4-5.
7. A battery cell, characterized in that, It includes a negative electrode and a positive electrode as described in claim 6.
8. An electrochemical device, characterized in that, Including the battery cell as described in claim 7.
9. An electronic device, characterized in that, It includes the electrochemical device as described in claim 8.
Citation Information
Patent Citations
Lithium supplement material and preparation method thereof, positive pole piece, battery and electric device
CN120073101A
Composite lithium supplement material and preparation method thereof, positive plate, battery and electric equipment
CN120600778A